For Goodwill, Aid and Economic Growth: The Funding of Academic Exchange Through the Swedish Institute, 1945–2010 - Åkerlund, Andreas (Nordic Journal of Educational History, 2015)
The article investigates the financial basis of state-sponsored international academic exchange through the Swedish Institute (SI). Founded in 1945 the SI is the main institution for Swedish public diplomacy and is as such part of modern foreign policy and Swedish soft power. This article maps the changing sources of funding as well as the sums spent on academic exchange from 1945–2010. It also discusses the various forms of exchange programs and gives an overview of the ideas behind and arguments for such programs. The overall picture is that state-sponsored exchange after 1945 has expanded. Not only has more and more money been spent on exchange, which led to an increase in the number of persons benefitted, but there has also been a diversification in exchange schemes towards parallel programs, each designed to fulfill a certain task. Though they fund different parts of the SI exchange scheme, the main sources of funding, however, have remained the same: the Ministry for Foreign Affairs, various development assistance agencies and programs as well as the Ministry for Education.